Development of 3D ELSA (3D E-Book Based on Scientific Literacy) on Temperature and Heat - Muhammad Zainal Arifin; Abd. Kholiq (IKIP Mataram, 2022)
ELSA 3D (E-Book 3D Based on Scientific Literacy) is an e-book teaching material that integrates scientific literacy as a medium in the learning process on temperature and heat materials. This type of development research uses the Hannafin and Peck model. The Hannafin and Peck model begins with a needs analysis followed by the design and development stage to create 3D ELSA media which expert lecturers then review. The 3D ELSA that has been reviewed and revised is then validated using a validation sheet to determine the validity of the 3D ELSA media covering several aspects. Then the implementation is carried out by conducting a learning process using 3D ELSA media to test the effectiveness and practicality of 3D ELSA media. Quantitative descriptive analysis was used as the method of analysis. Based on the results of the research that has been done, it can be concluded that the 3D ELSA that has been developed has a validity percentage of 93%, the response of students to the 3D ELSA is 96.3%, and the observation of learning implementation is 96.6%. So that the 3D ELSA is declared to be very valid and suitable to be used as a medium in the learning process on temperature and heat material. In addition, 3D ELSA is included in the medium category with an N-gain of 0.68, so using 3D ELSA as a learning medium is declared effective because it can improve scientific literacy skills.